PROBLEMATIKA KHITAN BAGI PEREMPUAN PERPEKTIF HADIS - Ilham Mustafa dan Ihdi Aini (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2020)
This article discusses the problem of circumcision for female. In general, Hadith prescribes circumcision  for female. But, in its application, the Islamic law for female circumcision can be sunnah, or permissible. The reason is the arguments that explain about female circumcision are few and it is not explained in detail and firmly.The problem of female circumcision in Indonesia is how to circumcise them, which is not in accordance with Islamic law. Although in principle, circumcision for female both gives benefits and also is not forbidden in Islam.